Weaving Religious and Cultural Values in the Curriculum Supervision Model of Taḥfīz Islamic Boarding Schools - Tri Wahyu Nurlia; Taufik Churrahman (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the curriculum supervision system at Islamic boarding school Taḥfīẓul Qur’an (PPTQ) Al-Madinatul Kamilah Sidoarjo, which integrates professionalism and spirituality within Islamic and cultural values. The research aims to develop a Value-Based and Culturally-Rooted Supervision Model that enhances both educational quality and teachers’ spiritual growth. Using a qualitative descriptive approach, data were collected through observation, interviews, and direct supervision, then analyzed using Miles and Huberman’s interactive model with triangulation. Findings reveal that supervision functions as a form of tarbiyah (nurturing), not administrative control. The process—through ḥalaqah observation, daily monitoring, weekly reflection, and spiritual coaching—emphasizes sincerity, discipline, and moral integrity. Rooted in uswah ḥasanah, iḥtirām, amānah, and ukhuwwah, this model fosters a non-hierarchical, reflective learning culture. It synthesizes managerial rationality and prophetic spirituality, showing that effective supervision is measured not by performance compliance but by spiritual and ethical transformation.